Fermented tofu dregs as a waste-derived biological feed resource for Pekin ducks (Anas platyrhynchos domesticus) - ASNAWI ASNAWI; DWI KUSUMA PURNAMASARI; VIDIA JUNIA AYU NINGGRUM; ADE YOGA PRATAMA; MUHAMMAD RIZQI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Asnawi, Purnamasari DK, Ninggrum VJA, Pratama AY, Rizqi M. 2026. Fermented tofu dregs as a waste-derived biological feed resource for Pekin ducks (Anas platyrhynchos domesticus). Biodiversitas 27 (3): d270314. https://doi.org/10.13057/biodiv/d270314. Tofu dregs, a protein- and mineral-rich by-product of tofu production, remain underutilized in duck feed due to high fiber content, anti-nutritional factors, and variable moisture that limit their direct inclusion in practical diets. This study evaluated the effects of EM4-based solid-state fermentation on the nutritional quality of tofu dregs and assessed the performance of Pekin ducks fed diets in which commercial feed was partially replaced with fermented tofu dregs. Fermentation improved the nutritional profile of tofu dregs by increasing crude protein, total fat, selected essential and non-essential amino acids, and several macro- and micro-minerals, while reducing crude fiber, moisture, and ash contents. Feeding trials were conducted using 100 Pekin ducks allocated to four dietary treatments containing 0%, 10%, 20%, and 30% fermented tofu dregs in isoenergetic and isonitrogenous rations. Increasing inclusion of fermented tofu dregs up to 30% did not significantly affect final body weight, body weight gain, or feed conversion ratio, although feed intake increased at higher inclusion levels. These findings demonstrate that EM4-fermented tofu dregs can be utilized as a sustainable waste-derived feed resource to partially replace commercial feed in Pekin duck diets without compromising growth performance. Integrating fermented tofu dregs into duck feeding strategies offers a practical approach to valorize tofu processing waste, reduce reliance on conventional feed ingredients, and support more circular and environmentally friendly duck production systems in regions where tofu dregs are abundantly available.